2016
DOI: 10.15766/mep_2374-8265.10518
|View full text |Cite
|
Sign up to set email alerts
|

Transgender Health: A Standardized Patient Case for Advanced Clerkship Students

Abstract: Introduction: Transgender patients experience poor health outcomes and often avoid seeking medical care because of negative encounters with providers. Despite growing awareness of the health disparities transgender patients face, there is very little curricular time in medical schools to improve medical students' knowledge and skills for caring for transgender patients. This standardized patient (SP) case was developed for use in a communication challenges workshop for advanced clerkship students in order to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 12 publications
0
53
0
Order By: Relevance
“…A review of LGBT health-specific undergraduate medical curricula in MedEdPORTAL revealed 14 dedicated modules, with three specifically aimed at addressing transgender health, [14][15][16] at the time of submission of this module. The majority of the LGBT health curricula published in MedEdPORTAL briefly cover transgender health disparities but do not address transgender-specific health care needs or treatment options.…”
Section: Citationmentioning
confidence: 99%
“…A review of LGBT health-specific undergraduate medical curricula in MedEdPORTAL revealed 14 dedicated modules, with three specifically aimed at addressing transgender health, [14][15][16] at the time of submission of this module. The majority of the LGBT health curricula published in MedEdPORTAL briefly cover transgender health disparities but do not address transgender-specific health care needs or treatment options.…”
Section: Citationmentioning
confidence: 99%
“…What is available is focused on preparing medical students uniprofessionally to conduct interviews and examinations with transgender patients using standardized patients or educational films. [7][8][9] Additionally, there is limited literature on interprofessional education (IPE) activities for health care learners to promote affirmative practice with transgender patients. The literature thus far has centered on health equity and uses case studies for discussion but does not highlight the use of standardized patients.…”
Section: Introductionmentioning
confidence: 99%
“… 20 Additionally, similar SP cases are being used across other medical disciplines for topics not well covered by the standard curriculum, such as LGBTQI care. 21 …”
Section: Discussionmentioning
confidence: 99%